Video Pembelajaran Wondershare Filmora Pada Materi Perkembangbiakan Tumbuhan - Mutiara Putty Padmasari; Sukian Wilujeng; Pramita Laksitarahmi Isrianto (Journal of Natural Sciences and Learning, 2022)
In the 21st century technological advances can support the improvement of thelearning process. By utilizing existing technology, teachers need to pay attention to aspectsof learning media in supporting the learning process. This research is an R&D (Researchand Development) development research which aims to produce appropriate and feasibledevelopment of natural science teaching materials (IPA) in junior high schools accordingto the validation results of material experts, media experts and student responses. Studentsbecome interested in studying and understanding the material provided.This development research leads to the ADDIE development model which consists of fivestages in research, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5)Evaluation. The technique of using data uses student response questionnaires. Data analysisused qualitative and quantitative descriptive analysis techniques